Rhinolith: A Case Report and Review of Literature - S Sudhakar; B Praveen Kumar; MPV Prabhat (Wolters Kluwer Medknow Publications, 2010)
Rhinoliths are calcareous concretions around calcinated intranasal foreign bodies within the nasal cavity. They are commonly seen in the anterior part of the nasal cavity and are diagnosed based on history and presenting illness. Developing lesions are usually asymptomatic and can be a supplementary finding during routine radiography. We report a case of rhinolith, found incidentally in a dental radiograph.